Hepatoprotective Potential of Pomegranate in Curbing the Incidence of Acute Liver Injury by Alleviating Oxidative Stress and Inflammatory Response - Ali, Hamid; Jahan, Azra; Samrana, Samrana; Ali, Abid; Ali, Safdar; Kabir, Nurul; Ali, Amjad; Ullah, Riaz; Mothana, Ramzi A.; Murtaza, Bibi Nazia; Kalim, Muhammad (Frontiers in Pharmacology, 2021)
Hepatitis is an inflammatory disease of the liver and considered as one of the leading causes of death worldwide. Due to its scavenging activity, Punica granatum may be used for the treatment and prevention of liver diseases. The current study investigated the protective mechanism underlying the effects of pomegranate against a rat model of carbon tetrachloride induced liver injury. Intraperitoneal injection of CCl4 resulted in liver inflammation, oxidative stress and accumulation of lipid in hepatocytes. CCl4 induced a downregulation of superoxide dismutase (SOD), glutathione (GSH) and melonaldehyde (MDA). Pomegranate protection was assessed in terms of biochemical parameters, histopathology and immunohistochemistry. Promegranate administration decreased inflammation, elevated serum enzymes, ROS production and countered the debilitating effects caused by CCl4. In addition, CCl4 induced histological changes were absent in the crude Promegranate extract group which also enhanced the scavenging activity of reactive oxygen species by enhancing the antioxidant defense mechanism as confirmed by detecting MDA, SOD and GSH expressions. The migration of CD68+ macrophages was halted at the injured area of the central vein and the number of macrophages were reduced to normal control by the crude extract compared to the positive control silymarin group. Likewise, protective effects of ethylacetate and aqueous fraction of crude extract were also observed. However, the butanol and n-hexane fractions displayed increased levels of ALT, AST and ALP as compared to silymarin. About 25% damage to hepatocytes was observed in the butanol and n-hexane group by histopathological examination which is a little better compared to the CCl4 treated group. The crude extract and its ethyl acetate and aqueous fractions may be accountable for the hepatoprotective potential of Punica granatum which was further confirmed by in vivo experiments. Together, these finding confirm that pomegranate exerts hepatoprotective activity against CCl4-induced oxidative stress and liver damage.